Effect of exenatide on peripheral nerve excitability in type 2 diabetes. Issue 10 (October 2021) - Issar, Tushar; Kwai, Natalie C.G.; Poynten, Ann M.; Arnold, Ria; Milner, Kerry-Lee; Krishnan, Arun V.
Highlights: Participants receiving exenatide therapy were observed to have normal peripheral nerve excitability in cross-sectional studies. Participants receiving DPP-IV or SGLT-2 inhibitor therapy demonstrated impairments in nerve excitability compared to controls. Exenatide therapy was associated with a normalisation of peripheral nerve excitability following a short duration of treatment. Abstract: Objective: To assess the effect of exenatide (a GLP-1 receptor agonist), dipeptidyl peptidase-IV (DPP-IV) inhibitors, and sodium-glucose co-transporter 2 (SGLT-2) inhibitors on measures of peripheral nerve excitability in patients with type 2 diabetes. Methods: Patients receiving either exenatide (n = 32), a DPP-IV inhibitor (n = 31), or a SGLT-2 inhibitor (n = 27) underwent motor nerve excitability assessments. Groups were similar in age, sex, HbA1c, diabetes duration, lipids, and neuropathy severity. An additional 10 subjects were assessed prospectively over 3 months while oral anti-hyperglycaemic therapy was kept constant. A cohort of healthy controls (n = 32) were recruited for comparison. Results: Patients receiving a DPP-IV or SGLT-2 inhibitor demonstrated abnormalities in peak threshold reduction, S2 accommodation, superexcitability, and subexcitability. In contrast, patients treated with exenatide were observed to have normal nerve excitability. In the prospective arm, exenatide therapy was associated with an improvement in nerve function as patients demonstrated corrections in S2 accommodation, superexcitability, and subexcitability at follow-up. These changes were independent of the reductions in HbA1c following exenatide treatment. Conclusions: Exenatide was associated with an improvement in measures of nerve excitability in patients with type 2 diabetes. Significance: Exenatide may improve peripheral nerve function in type 2 diabetes.